Perancangan Arsitektur Sistem Informasi Menggunakan Togaf ADM - Siska Nurul Marwiyah; Chandy Ophelia S; Suyanti (STMIK Budi Darma, 2023)
SMA Negeri 4 Sarolangun has not implemented information systems in every field such as academics, administration, libraries and infrastructure. The activities carried out in each of these fields are assisted by computers and there is no integrated information system between one field and another. So that accessing data together in each field cannot be done, besides that the data processing system currently used causes the required data and information to be not timely due to the difficulty of accessing data and information. For this reason, it is necessary to design an enterprise architecture using TOGAF ADM. TOGAF ADM is a method that can be used to design enterprise architectures. Each stage in TOGAF ADM can be carried out correctly if the business processes that exist within the organization really must be understood and able to be identified completely and correctly. This enterprise architecture modeling provides guidance in creating blueprints for the development of information systems for data, applications, business, and technology.